The Influence of Social Media Marketing and Brand Image on Brand Loyalty and its Impact on Consumer Purchase Decision with Store Atmosphere as A Moderation Variable (Case Study of XYZ Mall) - Kurniawan, Shelvy; Tanujaya, Novian (Business Economic, Communication, and Social Sciences Journal (BECOSS), 2024)
This research aims to obtain the results of the influence of Social Media Marketing, Brand Image, on Brand Loyalty and Consumer Purchase Decision with Store Atmosphere as a moderating variable. In this research, data was obtained by distributing questionnaires. The analytical method used in this research is SEM-PLS using SmartPLS 4 media. The research results show that Social Media Marketing has a significant effect on Brand Loyalty, Social Media Marketing has no significant effect on Consumer Purchase Decision, Brand Image has an effect significant effect on Brand Loyalty, Brand Image has no significant effect on Consumer Purchase Decision, Brand Image with Store Atmosphere as a moderating variable has no significant effect on Consumer Purchase Decision, Brand Loyalty has a significant effect on Consumer Purchase Decision.